Effectiveness and usability of an online tailored education platform for atrial fibrillation patients undergoing a direct current cardioversion or pulmonary vein isolation. (1st December 2018) - Desteghe, Lien; Germeys, Jana; Vijgen, Johan; Koopman, Pieter; Dilling-Boer, Dagmara; Schurmans, Joris; Delesie, Michiel; Dendale, Paul; Heidbuchel, Hein
Abstract: Background: Atrial fibrillation (AF) care should strive for more informed, involved and empowered patients. However, few effective educational programs are available. The aim of this study was to evaluate the effectiveness of an online tailored education platform to inform AF patients undergoing a direct current cardioversion (DCC) or a pulmonary vein isolation (PVI). Methods: 120 AF patients requiring DCC or PVI were allocated to an online education group ( n = 35), a standard care group despite having online access ( n = 36; randomized with group 1), and a group without a computer/tablet/smartphone receiving standard care ( n = 49). The Jessa Atrial fibrillation Knowledge Questionnaire (JAKQ), supplemented with procedure-specific questions, had to be completed 1–3 weeks before hospitalization, at hospitalization, and 6 and/or 12 weeks post-procedurally. Results: Major AF-related and procedure-related knowledge gaps were shown. The online tailored education group scored significantly better at hospitalization compared to baseline ( P = 0.001). This knowledge increase was retained after 6 ( P = 0.010) and 12 ( P < 0.001) weeks. In the online standard care group there was no change in knowledge from planning till hospitalization ( P = 1.000), although knowledge was improved 6 weeks post-procedurally ( P = 0.010). Knowledge did not improve in the group without computer/tablet/smartphone at any time ( P = 0.248). Most patients indicated that the platform was easy to use (87.9%), understandable (97.0%), and 72.7% indicated that an online platform was their preferred way to receive future AF-related information. Conclusions: Tailored online education is an effective strategy to improve AF- and procedure-related knowledge with lasting effects up to 12 weeks post-procedurally. The platform was positively evaluated by patients. Highlights: AF patients underestimate the risks associated with rhythm restoring procedures. AF patients overestimate the success rates of rhythm restoring procedures. Tailored online education is effective to improve AF- and procedure-related knowledge. The tailored online education platform is positively rated by patients.